Food Security and Women Case Study of Mahu Country on Saparua Island - Sahusilawane , Aphrodite Milana; Pattiselanno, August Ernst (Future Science / FSH-PH Publications, 2023)
Maintaining household food security is a way to overcome food insecurity. Women play an important role to make it happen, one of them is through household businesses. The research was conducted in Mahu Administrative Country on Saparua Island. The method used is descriptive analysis and field observation. Sampling was done purposively (purposive sample) of 24.40% (51 women) from 209 women of working age. The research objectives were (1) to find out the readiness of women to maintain household food security, (2) to find out about women's empowerment programs related to local food, (3) to find out the cooperation between the state government and the community regarding food security. The results showed: (1) household food security is still weak (2) women's empowerment programs have not been maximized, (3) coordination between the government and the community regarding food security needs to be improved.